Pengaruh Lab Matematika Virtual Terhadap Hasil Belajar Matematika Siswa SDN 80 Parepare - Denny Kurniawan; Nurhaedah P (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2023)
This study aims to determine that the use of the Lab Matematika Virtual application has a positive effect on mathematics learning outcomes for grade V students of UPTD SD Negeri 80 Parepare. This type of research is a quasi-experiment without a control class which is carried out in one group. The variables studied in this study were the mathematics learning outcomes of class V students of UPTD SD Negeri 80 Parepare as the dependent variable and learning by using the Lab Matematika Virtual application as the independent variable. The population of this research is all students of class V UPTD SD Negeri 80 Parepare for the academic year 2021/2022. Sampling was done by saturation sampling, the sample of this research is all students of class V. The instruments used in this research are learning outcomes tests and student response questionnaires that have been validated. Based on descriptive statistical analysis, the average value of mathematics learning outcomes before learning using the Lab Matematika Virtual application is 10 and the average value of mathematics learning outcomes after learning using the Lab Matematika Virtual application is 65,71. So it can be concluded that the use of the Lab Matematika Virtual application has a positive effect on mathematics learning outcomes in class V students of UPTD SD Negeri 80 Parepare.